How good are U.S. government forecasts of the federal debt? - Martinez, A (University of Oxford, 2014)
This paper compares annual one-year-ahead and five-year-ahead forecasts from government agencies for the U.S. gross federal debt and deficit from 1984 to 2013. Other studies have compared two of these agencies' forecasts, but not for debt. The current paper finds that the forecast from the Analysis of the President's Budget performs best across both horizons but does not encompass the other forecasts. Instead, each of the forecasts lacks information included by the other agencies and therefore a combination of all three outperforms any forecast individually.